C1 inhibitor function using contact‐phase proteases as target: evaluation of an innovative assay. Issue 9 (9th June 2015) - Ghannam, A.; Sellier, P.; Defendi, F.; Favier, B.; Charignon, D.; López‐Lera, A.; López‐Trascasa, M.; Ponard, D.; Drouet, C.
Abstract Background Controlling prekallikrein activation by C1 inhibitor (C1Inh) represents the most essential mechanism for angioedema patient protection. C1Inh function in the plasma is usually measured based on the residual activity of the C1s protease not involved in the pathological process. We have hereby proposed an alternative enzymatic measurement of C1Inh function based on contact‐phase activation and correlation with angioedema diagnostic requirements. Methods The contact phase was reconstituted using the purified components, with C1Inh standard or plasma sample. The kinetics of the amidase activity were monitored using Pro‐Phe‐Arg‐pNA, independently of alpha2‐macroglobulin. We prevented any interference from a possible high plasma kininogenase activity by preincubating the samples with protease inhibitor. Receiver operating characteristics (ROC) were used to calculate the assay's diagnostic performance. Results The calibration curve was built using C1Inh standard (threshold limit 0.10 × 10−3 U, i.e., 0.2 pmol), and C1Inh function was quantified in the sample, with a reference interval established based on healthy individuals (n = 281; men: 0.61–1.10 U/ml, median: 0.85 U/ml; women: 0.42–1.08 U/ml, median: 0.74 U/ml). The median values of female donors were lower than those of the others due to estrogen, yet C1Inh function remained within the reference interval. The ROC curve calculation provided the following optimum diagnostic cutoff values: women 0.36 U/ml (area under curve [AUC]: 0.99; sensitivity: 93.48%; specificity: 99.37%); and men 0.61 U/ml (AUC: 1; sensitivity: 100.0%; specificity: 100.0%). Conclusion The performance outcome provided features suitable for angioedema diagnostic or follow‐up. Established by means of the kinin formation process, this assay should be preferred over the method based on a C1s protease target.